Oxidative stress and lateral muscle development in Siberian Sturgeon (Acipenser baeri): preliminary observations. (International Journal of Health, Animal Science and Food Safety, 2016)
Embryonic development in bony fish is strongly influenced by environmental factors, mainly by temperature and dissolved oxygen, but little is known about their influence on Sturgeons. Since 1998 the international trade of Sturgeons has been regulated under CITES due to depletion of wild stocks. Sturgeon aquaculture as well as larvae production is, therefore, important because it may contribute to the repopulation of the wild stocks (Bronzi et al., 2011; Di Giancamillo et al., 2012).The aim of this study is to monitor oxidative stress status and muscle development during embryonic and precocious larval phases in Siberian Sturgeon (Acipenser baeri), when subjected to different incubating temperatures (13°, 16° and 19°C).Siberian sturgeon eggs were subjected to different incubation temperatures. Data regarding water quality parameters were recorded, as well as mortalities, embryonic period length, and precocious larvae behavior. Sampling was performed in the same developmental stage for each temperature, at five time points: 48 hours post-fertilization, embryo movements, hatching, schooling and yolk-sac full absorption. The observed hatching rates were between 85.5% and 98.8% with significant differences concerning the different experimental temperatures (T19 vs T13 and T19 vs T16, p
Keywords: Sturgeon; oxidative stress; muscle; temperature